ANALISIS BAHASA PADA STRATEGI PROMOSI SELEBGRAM @piitaak - Hartaty Malloni Marpaung; Saputri Dia Ningsih; Alfitri Dwi Rahmawati; Dinda Naura Nur Auliasari; Alya Mukhbita Meysun Athirah; Eni Nurhayati (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
In today's digital age, social media is growing at a rapid pace, making it accessible to all ages, from young to old. Instagram is one of the most widely used social media platforms. Instagram functions as a social media application that displays content mainly through photos and videos. The development of social activities on Instagram has led to many new things, one of which is the emergence of the word “celebgram”. The role of celebrities in marketing makes products/services easily recognized and known by the public because the celebrities themselves are already quite famous and known. This study aims to describe the language used in the Instagram account @piitaak and the impact of its use on the existence of Indonesian language. This research uses descriptive method because it can identify, describe, and analyze language errors in the Instagram promotion strategy of celebrity @piitaak. @pitaak account aka “Vita” likes to use a mixture of languages, between Indonesian and Javanese which is a characteristic of this celebrity from Gresik. it seems to be successful as one of its marketing strategies, so that it can establish a closer relationship with its followers.